(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
We have studied the effect of basic trap parameters and trap activation on the efficiency of capture of the males of the Citrus Mealybug Planococcus citri (Hemiptera: Pseudococcidae). The number of males caught by pheromone baited sticky traps was significantly affected by both size and type of trap. Generally plate traps caught more males than delta traps, and large traps caught more males than did the small ones. Significant dose response to sex pheromone in the range of 25-800mg was observed as high as lOOmg. Overdose repellence was not observed even when lures containing 800 mg of the pheromone were used. Three types of rubber septa were tested: American, French and Israeli dispensers. The tested doses were 200, 400, and 800mg and the dispensers were subjected to ageing under ambient conditions for 1,8,15, 22 and 29 days. The tested dispensers displayed a similar rate of release of the pheromone in the Iaboratory. However, these findings did not coincide with the level of male catch in the orchard. Traps baited with the French dispensers captured significantly fewer males than traps baited with the lsraeli and American ones. There were no significant differences between the tested three dosages. The catches, using the American dispensers, were uniform during the four weeks of ageing. This pattern of male catch is expected to last longer if lures containing 400mg or higher loads are to be used. Significantly, more males were caught by the traps suspended inside the trees than by those suspended between the trees or by those put further away from the study plot. The capture by the former traps did not differ from the capture by traps installed on the outer canopy or inside the canopy of Chlorpyrifos-treated trees. These findings suggest that the contribution of individuai trees to the level of the catch of traps is insignificant. lt is apparent that the male mealybugs fly toward the tree crown and only then start Iooking for the pheromone source. The results suggest that the abovementioned American dispensers fit both monitoring and mass trapping. High and continuous catches of males can be achieved using big plate traps baited with at least 200mg of the pheromone and suspended inside the tree crown.